The apprentice [videorecording (DVD)] - Sherman, Gabriel; Stan, Sebastian, 1982-; Strong, Jeremy, 1978-; Donovan, Martin, 1957-; Bakalova, Maria, 1996-; McNally, Catherine; Carrick, Charlie; Sullivan, Ben (Actor); Rendall, Mark, 1988-; Pingue, Joe (Relativity, 2024)
The Apprentice is a dive into the underbelly of the American empire. It charts a young Donald Trump's ascent to power through a Faustian deal with the influential right-wing lawyer and political fixer Roy Cohn.